Edukasi Personal Hygiene, Status Gizi, dan Kebugaran Jasmani pada SMP Negeri 2 Lawang - Yetty Septiani Mustar; Anna Noordia; Dita Yuliastrid; Anindya Mar’atus Sholikhah; Heri Wahyudi; I Made Wijaya; Riska Devi Kurniawati (Inspirasi Nusantara, 2023)
Health is an investment in the future of a nation as an important indicator of the quality of life. Most child health problems in schools can be prevented by promoting hygiene practices, nutritional status, and physical fitness through proper health education. This community service aims to educate students on personal hygiene, nutritional status, and physical fitness in schools to improve fitness, health status and quality of life. The method employed in this community service activity is the provision of materials accompanied by workshops and school mentoring. This activity is undertaken so that schools can be actively involved in integrating the implementation of educational programs on personal hygiene, nutritional status, and physical fitness. The outcomes of the activities that have been carried out demonstrate that the students and the school show a very good enthusiasm to participate in the whole series of activities from the beginning to the end. The school and students also evaluated that the community services team delivering material on personal cleanliness, nutritional status, and physical fitness were excellent and engaged. Through this activity, students increase their knowledge, build awareness, and learn to comprehend the need to practice personal cleanliness, consume a balanced diet, and engage in daily physical activity to preserve their health and fitness. In addition, students are committed to maintaining cleanliness, dietary habits, and fitness regularly.